The Influence of Family-Related Factors on Suicide in Major Depression Patients - Wang, Wei; Guo, Xin; Kang, Lijun; Zhang, Nan; Ma, Simeng; Cheng, Jing; Fang, Li; Liu, Zhongchun (Frontiers in Psychiatry, 2022)
Objective：To explore the influence of family-related factors on suicide-related behaviors of patients with depression, and to provide scientific basis for effective preventive measures. Methods：A total of 852 outpatients at Renmin Hospital of Wuhan University were enrolled in this cross-sectional study from April 2019 to January 2021. The general demographic information and family-related information of the patients were collected via a general information questionnaire, the Family Assessment Device, the Egna Minnen av Barndoms Uppfostran, and the Childhood Trauma Questionnaire. Results：Participants without suicide-related behaviors accounted for 10.45% of the total sample, those with suicidal ideations accounted for 47.54%, those with suicidal plans accounted for 24.77% and with suicidal attempts for 17.25%. Patients with depression who have lower education level, who were separated from their parents, who have severely impaired family function, who experienced childhood abuse, and whose parents adopted apathetic and severe child-rearing styles had a higher risk of suicide-related behaviors. In the multivariate regression model, degree of depression, education and child-rearing style were independent risk factors for suicide-related behaviors. Conclusion：Patients with depression who have been separated from their parents, have severely impaired family function, were abused in childhood or have been exposed to improper childrearing styles have a greater risk of suicide. Family-related factors play a predictive role in suicide in patients with depression. More attention should be paid to family-related factors to reduce the occurrence of suicidal ideation and attempt.